2016
DOI: 10.4025/actasciagron.v38i1.26021
|View full text |Cite
|
Sign up to set email alerts
|

<b>Priming and stress under high humidity and temperature on the physiological quality of <i>Brachiaria brizantha</i> cv. MG-5 seeds

Abstract: ABSTRACT. Palisade grass is a forage plant that is widely used in pasture cropping in the Brazilian savannah. The aim of this experiment was to evaluate palisade grass (Brachiaria brizantha cv. MG-5) seeds subjected to priming and stress at high humidity and temperature (before and after conditioning). The experimental design was completely randomized in a 2x5 factorial arrangement. Seeds were exposed to stress under high humidity and temperature (before and after conditioning) and five priming treatments [Wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 10 publications
3
17
1
1
Order By: Relevance
“…The benefits of priming by direct immersion for U. brizantha seeds have already been reported in the literature, both with water or other chemical agents (BATISTA et al, 2016a;BATISTA et al, 2016b). In this study, there was an additional benefit to the effect of priming using glucose during conditioning by direct immersion under germination.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The benefits of priming by direct immersion for U. brizantha seeds have already been reported in the literature, both with water or other chemical agents (BATISTA et al, 2016a;BATISTA et al, 2016b). In this study, there was an additional benefit to the effect of priming using glucose during conditioning by direct immersion under germination.…”
Section: Resultssupporting
confidence: 62%
“…Although not used on a large scale for major crops, seed priming has application in germplasm banks for small seed numbers (SILVA et al, 2016). Studies found in the literature have demonstrated that the priming of Brachiaria seeds increases the number of germinated seeds (CARDOSO et al, 2014), speed index (BINOTTI et al, 2014), and resistance to thermal stress (BATISTA et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
“…Priming may be performed with the use of substances that contribute to the expression of the seed physiological potential (Batista et al 2016). Seed priming may promote more balanced germination rates and higher germination speed, in addition to faster seedling growth under adverse conditions, for instance, under abiotic stress (Arif et al 2014).…”
Section: Palavras-chavementioning
confidence: 99%
“…However, few studies have been conducted on seed priming using the amino acid phenylalanine, which is a precursor of phenolic compounds that increase in response to different types of stress, e.g., related to the plant defense systems and adaptation to adverse situations (Stangarlin et al 2011). According to Batista et al (2016), priming with KNO 3 and Ca(NO 3 ) 2 enhance physiological seed quality, producing seeds with high tolerance to stress under high temperature.…”
Section: Palavras-chavementioning
confidence: 99%
“…The calcium nitrate solution can also be used in seed pretreatment to improve the germination process and act to overcome dormancy in some seeds (Silva et al, 2017). For example, in Brachiaria seeds, the dormancy is related to several factors, especially physical properties, and the priming with calcium nitrate resulted in higher tolerance of Brachiaria brizantha seeds to high humidity and high-temperature stress (Batista et al, 2016), thus being efficient in overcoming dormancy.…”
Section: Introductionmentioning
confidence: 99%